Paths 2 play: teacher’s play facilitation in Colombia - Nores, Milagros; Maldonado-Carreño, Carolina; Sánchez, M. Juliana; Escallón, Eduardo; Frede, Ellen (Frontiers in Education, 2023)
Introduction The quality of early childhood programs is essential for improving outcomes for children, and play-based practices are a vital component. However, the field is still trying to understand the role of teachers in facilitating play and their beliefs and practices related to play, as well as how to best support these practices. Methods Data was collected remotely between June and December 2021 using surveys from 55 teachers and video observations and interviews with directors, teachers, and parents at two aeioTU centers in Cartagena, Colombia. The study aimed to comprehend teachers’ understanding and practices of learning through play within a Reggio Emilia inspired program and its professional development supports. Results The study found that trainers, teachers, and parents generally viewed learning through play as a joyful, engaging, and socially interactive activity with a natural component. However, the study identified a misalignment between the sophisticated language on play used by trainers and teachers and the examples they provided for learning through play. Additionally, the study revealed a gap between the aeioTU curriculum’s comprehensive conceptualization of play and how teachers practice and self-report learning through play in their classrooms. The COVID-19 pandemic and limited policy definitions of play may have contributed to these findings. Discussion The study recommends that professional development programs focus on building teachers’ knowledge of play facilitation, helping them develop a nuanced understanding of play and its full spectrum and how it maps to their role in classrooms, and tracking the connection between playful experiences and children’s learning.